Konsistensi Puasa Senin-Kamis terhadap Self-control - Hanifah Nur Ilmi (UIN Sunan Gunung Djati Bandung, 2023)
Self-control is important for every individual. If the individual can control himself then he will be able to overcome his own problems. One way to control yourself is to fast Monday and Thursday. Our Monday fast can have a positive impact on individuals who carry it out. The results of several previous studies say that by fasting on Mondays and Thursdays, individuals are able to control themselves and their emotions. The meaning of our Monday fast is not only about holding back hunger, but also about holding back, holding back lust, and also holding back emotions. In this study, the authors will conduct research on the consistency of our Monday fasting on self-control. This research method is descriptive analysis. The data used for this writing material are interviews with 5 people who often fast on our Mondays as well as sources from other literature. The results of this study are that our Monday fasting can affect individual self-control. Individuals who frequently fast on Mondays can control themselves better than those who don't. This research is recommended to observe individual patterns that are consistent in fasting on Mondays and Thursdays and which are inconsistent.